The impact of good classroom management on students' attitudes in Islamic Religious Education learning - Safitri, Dian; Nurfuadi, Nurfuadi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2025)
Islamic educational philosophy plays a central role in shaping the character of Islamic boarding school students amid the complex challenges of the modern era, such as globalization, technological advances, and moral crises. This article aims to examine how basic concepts in Islamic educational philosophy can be used as a foundation for shaping the character of Islamic boarding school students to be noble, competitive, and relevant to the times. This research uses a qualitative method with a library research approach and descriptive-analytical analysis. Data was collected from classical and contemporary literature discussing Islamic educational philosophy, the values of tawhid, akhlak, and the integration of religious knowledge and science. The results of the study indicate that Islamic education based on philosophy emphasizes three main aspects: tauhid as a spiritual foundation, akhlak as a moral foundation, and knowledge as a means of social transformation. Additionally, Islamic boarding schools as educational institutions hold a strategic position in instilling these values through role modeling, habit formation, and a supportive environment. This study emphasizes the need for a holistic and adaptive educational approach so that pesantren education can produce students who are not only religious but also responsive to global challenges. This article contributes theoretically to the development of a character education model based on Islamic philosophy, while also advocating for the revitalization of the pesantren education system to remain contextual and transformative.